Primary repair versus diversion in penetrating colon injuries - Alhamdani, Adil Karim; Albadri, Jasim M.; Abed, Husham J.; Abed, Hadeel. J. (AL-Kindy College Medical Journal, 2013)
Back ground: In Iraq, after 2003 had more accidents of the shell, bullet and stab abdominal wounds, more over colon injuries. Objective: The aim of this study is to evaluate the most appropriate management of penetrating colon injuries, comparing the primary repair with the diversion. Methods: Eighty patient series with shell, bullet and stab colonic injuries during 4.5 years period from June 2006-december 2010 at Al-Yarmouk teaching hospital. The study compared the use of primary repair versus diversion, analyzing variables such as sex, age, severity of injury and mortality rate. Results: there were total 80 patients ,62 (77.5%) male and 18(22.5%) female .male :female ratio 3.4:1. the most affected age group was 21-30 years. 47 patients 58.75% were shell injuries.28 patients 35% were bullet injuries. 5 patients 6.25% were stab wounds. 46 patients 57.5% managed by primary repair ,one of them 1.25% died, while diversion in34patients 42.5% different grades of colon injuries ,5 of them 6.25% died ,this was due to different factors such as multiple organ injuries and post operative complications. Conclusion: the primary repair is safe and effective regarding morbidity and mortality in the management of grade II, III penetrating colon injuries with minimal risk factors as compared to diversion.